Introducing Android-based Digital Learning Media Assisted by iSpring Suite in Science and Social Studies Learning in Elementary Schools - Arifah, Arini Fakhria; Ubaidillah, Ubaidillah; Muhith, Abd (Journal of Educational Research and Practice, 2025)
This study examines the Implementation of Android-based digital learning media developed using iSpring Suite at MIN 3 Jember for IPAS learning in the fourth grade. The study aims to enhance students' understanding of abstract concepts through an interactive application integrating visual animations, quizzes, and curriculum-aligned learning materials. Despite the growing adoption of digital learning tools, there remains a gap in research on their effectiveness in improving conceptual understanding in elementary education. This study addresses that gap by evaluating the impact of an offline-accessible application designed to overcome challenges related to limited devices and unstable internet connections. This research used a qualitative approach with a case study design conducted at MIN 3 Jember, an Islamic school in East Java. The subjects were 30 fourth-grade students and an IPAS teacher. Data were collected through observation, interviews, documentation, and field studies. Observations focused on student interactions, learning media use, and responses. Interviews explored teachers' and students' experiences. Documentation included syllabi, lesson plans, and learning materials. Data were analyzed using Miles and Huberman's interactive model, involving data reduction, presentation, and conclusion verification through triangulation. The findings indicate that the application improves students' comprehension of abstract concepts like the water cycle while enhancing motivation and engagement. However, infrastructure limitations persist, necessitating better resources and teacher training. Overall, this study highlights the effectiveness of Android-based digital learning media in fostering engaging learning experiences and provides recommendations for educators and developers.